Life in a Diverse Oral Community – Strategies for Oxidative Stress Survival - Henry, Leroy G. (J Oral Biosci, 2014)
BACKGROUND: While the oral cavity harbors more than 680 bacterial species, the interaction and association of selected bacterial species play a role in periodontal diseases. Bacterial species including Porphyromonas gingivalis, Treponema denticola and Tannerella forsythia, a consortium previously designated as the “red complex” is now being expanded to include other new emerging pathogens that are significantly associated with periodontal disease. HIGHLIGHT: In addition to novel mechanisms for oxidative resistance of individual species, community dynamics may lead to an overall strategy for survival in the inflammatory environment of the periodontal pocket. Complex systems controlled by response regulators protect against oxidative and nitrosative stress. CONCLUSION: The combination of these multifaceted strategies would provide a comprehensive defense and support system against the repetitive host immune response to promote microbial persistence and disease.